“Leadership and Smart Environment Policy” Studi Kasus Implementasi Smart Environment di Pekanbaru - Yendra Erison; Ahmad Sholikin; Midkholus Surur; Halimur Rosyid; Nur Habibah (Universitas Islam Darul Ulum Lamongan, 2023)
This research aims to analyze Leadership and Smart Environment Policy: A Case Study Implementation of Smart Environment in Pekanbaru. One of the problems that is still a frightening threat to the sustainability of the environment and people's lives in the future. Pekanbaru City is one of the big cities in Indonesia, located in Riau Province. With the significant increase in population, the environmental problems experienced in Pekanbaru City, Riau Province are very complex, starting from the accumulation of rubbish, floods, forest fires, pollution and so on. The research uses descriptive qualitative research methods with a library research approach as the basis for researchers in this journal, by conducting in-depth reviews of national journals and references that are reputable and can be accounted for in the accuracy of data information. The result of this research is the application of a smart environment to create an environment that provides comfort for its residents, beauty for those who see it both materially and immaterially, and resource conservation in an effort to reduce urban waste can be said to be successful. So it can create a smart environment. The aim of a smart environment is to be able to change a colony that was originally dirty, smelly and filthy into a colony that is clean, comfortable and attractive. Therefore, a smart environment policy is needed to create a green city in Pekanbaru City.